Use of posterior belly digastric branch of the facial nerve to identify facial nerve trunk in doing parotidectomy - Jyotirmoy Phookan; Bijit Kumar Saikia; Taufeequl Islam; Bibhuti Das; Rakesh Talukdar (Elsevier, 2024)
Introduction: The identification of the Facial nerve in parotid surgery stands as a stiff challenge till date. Various different pointers with numerical measurements have been identified. But these landmarks can differ between various race, sex or the presence of a tumour. Tracking the branch to posterior belly of digastric, which is not an expressive branch is the only surgical step where the surgeon can reach the facial nerve trunk without doing any surgical maneuver on facial nerve trunk. Materials and methods: The study was conducted on 15 patients presenting with disease of the parotid gland. Surgery was done by following appropriate surgical steps and the nerve to posterior belly of digastric was searched for. Signs of Facial nerve palsy post-surgery was looked for and noted. Results: In all our patients we could find the PDBFN confidently in continuation of the surgery. We observed the PDBFN is a thicker nerve then the marginal mandibular and it's easier to identify if it is intended as it is a constant anatomical landmark. Use of this branch help us to track the nerve which is definitive. Conclusion: We found the digastric branch of the facial nerve is a reliable, consistent landmark to get the facial nerve trunk. Moreover, it was identified without any manouvere over the facial nerve trunk and as it is a non-expressive branch, it guards the possibility of inducing morbidity.